Talfiq In The Fatwa Of The National Sharia Council-Indonesian Ulema Council (DSN-MUI) Regarding Syirkah - Anas Bayan Mubarok; Sofian Al Hakim; Muhamad Izazi Nurjaman (Prodi Hukum Ekonomi Syariah Fakultas Agama Islam, Universitas Muhammadiyah Purwokerto, 2024)
This article discusses the ikhtilaf of Hanafiyah, Malikiyah Shafi'iyah and Hanabilah related to musharakah/shirkah and talfiq contracts in the determination of DSN-MUI fatwas on shirkah. The method used in this study is a descriptive method of analysis with a qualitative approach. The data sources used come from books, books, journals, the internet, theses and fatwas related to the shirkah contract. The results of the research in the article are: first, the DSN-MUI Fatwa on shirkah does not refer to one particular group of madhab scholars, but there are different opinions taken from one circle of scholars only there are opinions taken from the number of ulama and most of them come from jumhur. Secondly, it can be said that if there is talfiq in this fatwa about shirkah, the talfiq referred to here is to take some opinions from madzhab scholars in one qadliyah namely about shirkah. Â Â About the definition and determination of the profit ratio in shirkah taking the opinion of Hanafi scholars, as for the rukun of the death contract, opinions taking jumhur opinions other than Hanafi scholars, and about the type of shirkah more likely to use the opinions of jumhur ulama. Â Third, talfiq in this fatwa can be classified as talfiq which is allowed by some scholars, not talfiq which causes obscurity of shirkah law, not talfiq in playful motives and not necessarily just taking the easy.